Associations between EBV and CMV Seropositivity, Early Exposures, and Gut Microbiota in a Prospective Birth Cohort: A 10-Year Follow-up - Carvalho-Queiroz, Claudia; Johansson, Maria A.; Persson, Jan-Olov; Jörtsö, Evelina; Kjerstadius, Torbjörn; Nilsson, Caroline; Saghafian-Hedengren, Shanie; Sverremark-Ekström, Eva (Frontiers in Pediatrics, 2016)
Early-life infections with persistent Epstein-Barr virus (EBV) and cytomegalovirus (CMV) are delayed in affluent countries, probably due to alterations in early environmental exposures, such as maternal age, siblings and day care attendance. We have previously reported that the timing of EBV and CMV contraction is related both to allergic sensitization and changes in functional competence of immune cells, while the presence/absence of lactobacilli (Lactobacillus (L.) casei, L. paracasei and L. rhamnosus) or Staphylococcus (S.) aureus in faeces is related to the risk for allergy. Here, we used the same prospective longitudinal birth cohort of children to investigate early-life environmental exposures, and their influence on EBV and CMV contraction over time. Since gut microbes also belong to this category of early exposures, we investigated their association with herpesvirus contraction. Our results show that these two viruses are acquired with different kinetics and that EBV and CMV seroprevalence at 10 years of age was 47% and 57%, respectively. We also observed that a delayed EBV or CMV infection was associated with older maternal age (time ratio (TR) 1.14, CI (95% confidence interval) 1.07-1.21, Padj<0.001 and TR 1.09, CI 1.03-1.16, Padj=0.008, respectively). Further, we present the novel finding that S. aureus colonization reduced the time to CMV acquisition (TR 0.21, CI 0.06-0.78, Padj=0.02). Together, these findings suggest that there is a relationship between timing of herpesvirus acquisition and early-life immune modulating exposures, which interestingly also includes the early infant gut microbiota.